Multisystem inflammatory syndrome in a neonate with severe hemophilia - a diagnostic challenge in COVID times: a case report - Sumitha Arun; Taliya Grace Cherian; Chepsy Philip (BMC, 2022)
Abstract Background Multisystem Inflammatory Syndrome in Neonates (MIS-N) can occur following antenatal COVID- 19 infection in the mother. Here we report a rare case of a neonate with Hemophilia A and MIS-N. Case presentation A 2-day-old baby presented with an intramuscular hematoma, neonatal seizures, and isolated activated partial thromboplastin time (APTT) prolongation. The neurosonogram showed a subdural hematoma. A diagnosis of Hemophilia A was made and was confirmed by factor 8 assay and genetic analysis. Supportive measures and Factor 8 replacement was initiated. A rising trend of inflammatory markers and an ongoing need for mechanical ventilation were noted. As there was a history of COVID-19 in the mother in the third trimester, MIS-N was diagnosed. The baby was treated with intravenous immunoglobulin (IVIG) and steroids, and there was an improvement in the clinical and laboratory markers. However, the baby developed seizures on day 16. There was an increase in the subdural hemorrhage and a further rise in inflammatory markers. A craniostomy and hematoma evacuation was done and the baby improved. Conclusion The concurrent occurrence of hemophilia A with intracranial bleed, and MIS-N in a neonate is a diagnostic challenge. It is important to have a high index of suspicion to ensure timely diagnosis and treatment of MIS-N in this pandemic era.